Role Reversal and Women’s Violence against Men in Amma Darko’s The Housemaid - GBAGUIDI, CELESTIN (My University, 2018)
Women’s domination over men is now noticeable in many parts of the world. Domination in the context of marriage is mostly seen as the supremacy of men over women. Very often, women only are perceived to be the victims of domestic violence and to undergo decisions made by men who are seen as the decision makers, the family leaders, and the perpetrators of violence in marriages. Consequently, female hegemony over men remains untold in many African societies. This role reversal is noticeable in Amma Darko’s The Housemaid through husbands’ battery and maltreatment and the leadership of women. Through the lenses of the reader-oriented theory, this paper investigated the method through which Darko makes available the phenomenon of women’s supremacy over men. It also argued that with the advent of women’s domination over men, mankind slowly and surely attempts an effective deconstruction of the patriarchal status exclusively dedicated to men. Violence and decision making are no longer the privilege of men as women are changing the role in a male-controlled society.
Keywords: domination; violence; female hegemony; male victims; patriarchal status